Forestación de bosques en sabanas de la altillanura colombiana. Relevancia de las condiciones ambientales para el establecimiento de plántulas (2017)
One way to counteract climate change is to plant forests with high carbon storage capacity. In this study we report the results of a reforestation project in savannas of the Tomogrande Reserve, in Vichada Department, Colombia. We restricted fire in six one-hectare plots: in two seasonally inundated and two highland savannas we planted seedlings of trees found in the Orinoco Basin and nearby gallery forests and in two of them we did not plant seedlings (control plots). Out of 200 seedlings planted in well-drained savannas, only 17 % survived after two and a half years (33 % came from nearby forest and 12 % from other areas). None of the 182 seedlings planted in flooded savannas survived at the end of the study. The main mortality cause in well-drained savannas was wilting. We concluded that in addition to the control of fire, seedling establishment of forest trees in savannas is highly affected by climatic and light conditions and for this reason the trees with highest potential for restoration are the ones already found at the site in the same ecological conditions (e.g. forest edge).